Clinical and neuropathological associations of plasma Aβ42/Aβ40, p‐tau217 and neurofilament light in sporadic frontotemporal dementia spectrum disorders - Binita Rajbanshi; Igor Prufer Q C Araujo; Lawren VandeVrede; Peter A. Ljubenkov; Adam M. Staffaroni; Hilary W. Heuer; Argentina Lario Lago; Eliana Marisa Ramos; Leonard Petrucelli; Tania Gendron; Jeffrey L. Dage; William W. Seeley; et al. (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract INTRODUCTION Plasma amyloid beta42/amyloid beta40 (Aβ42/Aβ40) and phosphorylated tau217 (p‐tau217) identify individuals with primary Alzheimer's disease (AD). They may detect AD co‐pathology in the setting of other primary neurodegenerative diseases, but this has not been systematically studied. METHODS We compared the clinical, neuroimaging, and neuropathological associations of plasma Aβ42/Aβ40 (mass spectrometry), p‐tau217 (electrochemiluminescence), and neurofilament light ([NfL], single molecule array [Simoa]), as markers of AD co‐pathology, in a sporadic frontotemporal dementia (FTD) cohort (n = 620). RESULTS Aβ42/Aβ40 showed no clinicopathological associations. High p‐tau217 was present in amnestic dementia (AmD) presumed to be due to FTD, logopenic primary progressive aphasia (lvPPA), and APOEε4 carriers, and correlated with worse baseline and longitudinal clinical scores, lower hippocampal volumes, and more severe AD co‐pathology (Braak Stage). NfL was elevated in all FTD phenotypes, and correlated with clinical scores and frontotemporal brain volumes. DISCUSSION Plasma p‐tau217 has clinical, neuroimaging, and neuropathological correlates in sporadic FTD and may identify FTD cases with AD co‐pathology. Highlights Alzheimer's disease (AD) features could be identified with plasma phosphorylated tau217 (p‐tau217) in frontotemporal lobar degeneration (FTLD). Plasma p‐tau217 is a better discriminator of AD co‐pathology and AD‐associated features in FTLD than plasma amyloid beta42/amyloid beta40 (Aβ42/Aβ40) and neurofilament light (NfL). In FTLD, plasma p‐tau217, but not Aβ42/Aβ40 or neurofilament light, has phenotypical, neurocognitive, and neuroimaging correlates suggestive of AD co‐pathology.